Pengaruh Pendekatan Teaching at The Right Level Terhadap Kemampuan Menulis Teks Eksposisi Di Siswa Kelas SMA Negeri 1 Malingping - Agustin, Dewi Puspita (Universitas Mathla'ul Anwar Banten, 2025)
This researh was This research was conducted based on the issue of low writing skills, particularly in writing expository texts among tenth-grade students, who still face difficulties in expressing their ideas in well-structured written form. The purpose of this study is to determine the difference in the effect of the Teaching at the Right Level approach compared to the Culturally Responsive Teaching approach on students’ ability to write expository texts. This study employs a quantitative research method. The population consists of 396 tenth-grade students of SMA Negeri 1 Malingping, and the sample used in this study comprises 72 students from two classes, selected through random sampling. The research instrument used is a writing skills test for expository texts, which includes both pretests and posttests. Based on the results of this research, it can be concluded that there is an effect on students’ expository writing skills between those who were taught using the Teaching at the Right Level approach and those taught using the Culturally Responsive Teaching approach. This conclusion is supported by the results of the hypothesis test, which used an Independent Samples Test and obtained a significance value of 0.039 < 0.05, indicating that H0 is rejected and H1 is accepted. Therefore, it can be stated that there is a significant difference in the influence of the Teaching at the Right Level approach on the expository writing skills of tenth-grade students at SMA Negeri 1 Malingping.